The jet detection in radio-loud narrow-line Seyfert 1 galaxies. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Gu, Minfeng
Abstract: With relatively small black hole masses and high accretion rates, narrow-line Seyfert 1 galaxies are thought to be young AGNs. About 7% of them are radio-loud narrow-line Seyfert 1 galaxies (RLNLS1s). RLNLS1s allow us to re-address some of the key questions regarding the physics of jet formation. As the first step of the systematic study on the jet properties of RLNLS1s, we present the radio structure of fourteen RLNLS1s from VLBA observations at 5 GHz in 2013. Although all these sources are very radio-loud with R > 100, their jet properties are diverse, in terms of their pc-scale morphology and overall radio spectral shape. The core brightness temperatures of our sources are significantly lower than those of blazars, therefore, the beaming effect is generally not significant, compared to blazars. This implies that the bulk jet speed may likely be low in our sources.